Association of Homocysteine Levels with Recurrent Pregnancy Loss: A Systematic Review: Homocysteine Levels with Recurrent Pregnancy Loss - Kalsoom, Rizwana; Mahmood, Anjum; Soomro, Shabana Bano; Fida, Najma; Arif, Amena; Amer, Ahsan (Pakistan Journal of Health Sciences, 2025)
Elevated homocysteine (Hcy) has been implicated in placental vascular dysfunction and adverse reproductive outcomes. Objective: To synthesize recent evidence on the association between Hcy levels and recurrent pregnancy loss (RPL), emphasizing methodological consistency and potential modifiers. Methods: Following PRISMA 2020, observational studies comparing Hcy in women with RPL versus controls were screened across PubMed, Scopus, and Cochrane. Reviews, pilots, case reports, abstracts, animal studies, and articles without quantitative Hcy data were excluded. Risk of bias was assessed using the Newcastle–Ottawa criteria; results were summarized with Synthesis Without Meta-analysis (SWiM). Results: Fourteen eligible studies across South Asia, the Middle East, Europe, and East Asia consistently reported higher Hcy among RPL cases, with typical mean differences =4–7 µmol/L and odds ratios ≈2–3, including studies adjusting for folate/B12 and MTHFR genotype. Heterogeneity stemmed from biospecimen type (serum/plasma), assay platform (HPLC vs immunoassay), fasting status, sampling time (preconception vs early pregnancy), and cut-offs (10–15 µmol/L). Emerging literature outside the included set supports endothelial mechanisms and gene nutrient interactions while highlighting reporting gaps and the need for interventional trials. Conclusions: Current evidence supports Hcy as a reproducible risk marker for RPL, plausibly mediated by endothelial and thrombo-inflammatory pathways and modified (but not fully explained) by folate/B12 status and genetic variants. Standardized measurement, rigorous adjustment, and randomized trials of targeted vitamin strategies are priorities.